THE MANAGEMENT OF THE PANDEMIC COVID-19 CRISIS BY QUEBEC SCHOOL PRINCIPALS: PRACTICES, ISSUES AND LEARNINGS - Jean BERNATCHEZ; Olivier LEMIEUX; Anne-Michèle DELOBBE (Universitaria Publishing House, Craiova, 2021)
Our study focuses on the management of schools in the context of a pandemic. School principals in Quebec are faced with the management of the COVID-19 pandemic crisis in 2020 and 2021, without having any prior training or experience in crisis management. What practices did they deploy in response to the urgency of the situation? What issues were brought to light? What have they learned that could be useful in the future? Our article aims to answer these three questions, after having posed the problem and defined the concepts. The research strategies used were a literature review of scientific documents on crisis management and the profession of school management; a monitoring of current events in the school sector; and semi-structured interviews (N=15) with school principals. In terms of practices, eight management principles are identified, related to financial and human resources, leadership, planning and communication. In terms of issues, those of an administrative and pedagogical nature emerge. In terms of learning, several skills developed in the context of managing the COVID-19 crisis can have a positive, lasting effect on the practices of school principals.